OOoswitch : 501 things you wanted to know about switching to OpenOffice.org from Microsoft Office - Granor, Tamar E. (Hentzenwerke Pub., 2003)
"As Microsoft Office users are converting to OpenOffice.org in droves, due to a wide difference in price and no onerous licensing or restrictive installation and activation requirements, this timely guide to making this switch helps MS Office users get up to speed quickly.